(untitled) (Pulse, 2024)
Molecular diagnostic (MDx) techniques have revolutionized the field of clinical diagnostics, providing several advantages over traditional microbial culture methods. The ability to perform multiplex molecular panel tests is a significant advancement that allows for the simultaneous detection of multiple pathogens from a single specimen. Multiplex panels are available for various types of infections, including respiratory, gastrointestinal, urinary, and sexually transmitted infections. This versatility makes them valuable tools in different clinical scenarios. The integration of these advanced diagnostic tools into routine clinical practice holds great promise for improving patient outcomes and public health. Pulse Vol.16, 2024 P: 26-30